Translating from Memory: Patrick Modiano in Postmodern Context - Timothy H. Scherman (Studies in 20th & 21st Century Literature, 1992)
In this essay I have attemped to renegotiate the relationship between the work of Patrick Modiano and the conditions of literary production designated by "postmodernism." Contemporary French reviewers and critics have greeted with guarded praise Modiano's efforts to write in a language and about events that belong to another writing. Following their lead, this essay first explores the tension (often lost on American readers) created by the possibility that the historical referent of Modiano's texts—not only Modiano's personal past but the horror of the Occupation—might now exist only as a weightless narrative "effect." As such, it is a part of style somehow comparable to and manipulable by a postmodern, purely textural hermeneutic. As many critics have pointed out, Modiano reveals his awareness of this problem through his obsessive thematizing of "memory." My argument here is that by employing a specifically translational mode ofwriting that would co-opt the "loss of loss" characteristic of postmodernism, Modiano is able to renew our sense of the jagged reality of history as always remembered by a finite subjectivity. I demonstrate this translational mode in an analysis of Modiano's Rue des boutiques obscures, in which we find not only the patently postmodern and self-referential detective story form, but the textually invoked subject of that form, presented as "translations" that imply historically lost but nonetheless palpable, real, and at times horrible, antecedents.
Keywords: Patrick Modiano; postmodernism; language; American readers; Occuation; hermeneutics; memory; translational mode; Rue des boutiques obscures; detective story; translations